On the variability of the McGurk effect: Audiovisual integration depends on prestimulus brain states - Keil, Julian; Müller, Nadia; Ihssen, Niklas; Weisz, Nathan (Cerebral Cortex, 2012)
The McGurk effect demonstrates the influence of visual cues on auditory perception. Mismatching information from both sensory modalities can fuse to a novel percept that matches neither the auditory nor the visual stimulus. This illusion is reported in 60-80% of trials. We were interested in the impact of ongoing brain oscillations - indexed by fluctuating local excitability and interareal synchronization - on upcoming perception of identical stimuli. The perception of the McGurk effect is preceded by high beta activity in parietal, frontal, and temporal areas. Beta activity is pronounced in the left superior temporal gyrus (lSTG), which is considered as a site of multimodal integration. This area is functionally (de)coupled to distributed frontal and temporal regions in illusion trials. The disposition to fuse multisensory information is enhanced as the lSTG is more strongly coupled to frontoparietal regions. Illusory perception is accompanied by a decrease in poststimulus theta-band activity in the cuneus, precuneus, and left superior frontal gyrus. Event-related activity in the left middle temporal gyrus is pronounced during illusory perception. Thus, the McGurk effect depends on fluctuating brain states suggesting that functional connectedness of left STS at a prestimulus stage is crucial for an audiovisual percept. © The Author 2011. Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: illusion; MEG; multisensory; perception